Toilet Training for Children with Moderate Intellectual Disabilities: Influence of Modeling Technique - Siti Jaleha; Nurbayti Rahmah (Universitas Lambung Mangkurat, 2026)
Toilet training is an important aspect in the development of children at toddler age and must receive parental attention when urinating and defecating. Based on preliminary studies, it was found that not all children with disabilities are ready to undertake toilet training when they are 5 years old. Data show that of 35 children with intellectual disabilities, 21 children were unable to use the toilet, 19 children were unable to clean themselves after urinating, and 24 children were unable to clean themselves after defecating. This study aims to determine the effect of modeling techniques on the success of toilet training in children with moderate intellectual disabilities. This research uses an experimental method in the form of Single Subject Research (SSR) with an A-B design. The subjects of this research were 5 children with moderate intellectual disabilities at SLB Negeri 3 Banjarmasin. The data obtained were analyzed using visual graphics analysis techniques. The modeling technique was carried out by providing education to parents and children by displaying pictures and direct practice of implementing good and correct toilet training. Modeling techniques can positively increase the success of toilet training. The results of the study showed that five children's toilet training abilities significantly increased from the baseline phase (A) to the intervention phase (B) after being given intervention using modeling techniques.